2017
DOI: 10.1016/j.compstruct.2017.09.081
|View full text |Cite
|
Sign up to set email alerts
|

The effect of z-binding yarns on the electrical properties of 3D woven composites

Abstract: This is a repository copy of The effect of z-binding yarns on the electrical properties of 3D woven composites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…Comparing the ultimate compressive load in the case of the baseline specimens (see Table 2) clearly reflects the effect of crimp in 2D and 3D woven composites. This crimp effect has been the scope of many research studies in the literature [9,11,28,[38][39][40], and it confirms the trend observed in this study. NCF with the least waviness exhibits the maximum compressive strength (see Table 2), followed by the 2D-PW, then the ORT-TW and the ORT-PW withstanding the least compressive load to failure.…”
Section: Load-displacement Responsesupporting
confidence: 91%
“…Comparing the ultimate compressive load in the case of the baseline specimens (see Table 2) clearly reflects the effect of crimp in 2D and 3D woven composites. This crimp effect has been the scope of many research studies in the literature [9,11,28,[38][39][40], and it confirms the trend observed in this study. NCF with the least waviness exhibits the maximum compressive strength (see Table 2), followed by the 2D-PW, then the ORT-TW and the ORT-PW withstanding the least compressive load to failure.…”
Section: Load-displacement Responsesupporting
confidence: 91%
“…There is general acceptance that the current practice of designing a damage tolerant structure is to take advantage of composite material heterogeneity and to configure the material such that it will withstand certain types of damage and will naturally arrest their propagation; 3D fibre architectures [16][17][18] and resins modified with nano particles [19][20][21][22] have been used in that effort. Yet, this is a passive approach and for this reason it is subject to its own limitations.…”
Section: Assessment Of the Health Of A Structurementioning
confidence: 99%
“…For woven composites, literatures about ERM in both plain and 3D woven structures have been reported and the effects of the structures on sensing property have been studied through experimental method. 20,21 However, the results of ERM method usually reflect a vague relation between the location of geometric change and resistive property. This is caused by the CFs in the FRPC materials, such as prepregs, that are arranged into an entirety, which makes the whole structure to become a resistor network.…”
Section: Introductionmentioning
confidence: 99%
“…For woven composites, literatures about ERM in both plain and 3D woven structures have been reported and the effects of the structures on sensing property have been studied through experimental method. 20,21…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation